2022
DOI: 10.2337/dc22-1148
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonists and the Risk of Thyroid Cancer

Abstract: OBJECTIVE To determine whether use of glucagon-like peptide 1 (GLP-1) receptor agonists (RA) is associated with increased risk of thyroid cancer. RESEARCH DESIGN AND METHODS A nested case-control analysis was performed with use of the French national health care insurance system (SNDS) database. Individuals with type 2 diabetes treated with second-line antidiabetes drugs between 2006 and 2018 were included in the cohort. All … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 17 publications
0
42
1
3
Order By: Relevance
“…Previous findings regarding possible pro-oncogenic characteristics of GLP-1 RA have been inconsistent. Several studies have shown that incretin-based drugs are associated with increased risk of multiple cancer types 8 , 22 24 . A recent real-world study using FAERS data from the first quarter of 2004 to the second quarter of 2020 reported significant signals between GLP-1RA and certain tumors, including medullary thyroid cancer, papillary thyroid cancer, malignant pancreatic neoplasms, islet cell neoplasms and APUDoma NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings regarding possible pro-oncogenic characteristics of GLP-1 RA have been inconsistent. Several studies have shown that incretin-based drugs are associated with increased risk of multiple cancer types 8 , 22 24 . A recent real-world study using FAERS data from the first quarter of 2004 to the second quarter of 2020 reported significant signals between GLP-1RA and certain tumors, including medullary thyroid cancer, papillary thyroid cancer, malignant pancreatic neoplasms, islet cell neoplasms and APUDoma NEC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent nested case‐control study by Bezin et al 11 using the French health insurance claims database, reported an increased risk of thyroid cancer with GLP‐1RAs (adjusted HR 1.58, 95% CI 1.27‐1.95). A nested case‐control design and risk set sampling were applied to that study to minimize potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the analysis of cases reported in the European Pharmacovigilance Database showed that the use of GLP-1 analogs is associated with a higher risk of developing thyroid cancer [ 126 ]. In a recently published study, which analyzed a total of 2526 cases of patients with thyroid cancer compared with 45,184 people from the control group, it was shown that the use of GLP-1 analogs for 1–3 years was associated with an increased risk of all thyroid cancers [ 127 ]. Attention should also be paid to the increased risk of tachycardia and arrhythmia during treatment with semaglutide [ 128 ].…”
Section: Treatment Of Obesitymentioning
confidence: 99%